Geochronology, petrogenesis, and tectonic characteristics of a volcanic–intrusive complex on the northern margin of North China Craton and its limitation on the closing time of the Paleo-Asian Ocean (245 Ma) - Sen Wang; Hong-jie Qu; Shuan-hong Zhang; Huan Wang; Meng-ying Cai; Ge-xue Zhao (China Geology)
ABSTRACT: The Central Asian Orogenic Belt (CAOB) is one of the largest and best preserved accretionary type orogenic belts in the world. Due to its complex tectonic history, the timing and location of the final closure of the Paleo-Asian Ocean and its tectonic evolution have been hotly discussed. To determine the petrogenesis and tectonic characteristics of the poorly exposed Triassic volcanic-intrusive complex on the northern margin of the eastern North China Craton, the authors conducted a study of zircon Lu-Hf isotopes, integrated with zircon U-Pb dating and whole-rock geochemistry. Zircons from eight representative volcanic and intrusive samples yielded concordant U-Pb ages of 251–245 Ma. The volcanic and intrusive rocks are all characterized by enrichments in large ion lithophile elements and depletions in high field strength elements, and they have features similar to those of highly fractionated I-type granites. The εHf(t) values for the volcanic and intrusive rocks, respectively, range from –1.69 to +3.75 (mean=+1.22) and –2.17 to +3.15 (mean=+0.38), with two-stage model ages of 1035–1345 Ma (mean=1196 Ma) and 1073–1401 Ma (mean=1250 Ma). The Hf isotopic features indicate that these rocks were formed by partial melting of young crustal material that was newly accreted from the depleted mantle, together with a degree of contamination by other crustal material. The volcanic–intrusive complex was related to an active continental margin in a volcanic arc and syn-collisional setting, indicating that the Paleo-Asian Ocean was closed after the Middle Triassic (245 Ma) along the northern margin of the North China Craton. This provides a constraint on the timing of the change in tectonic setting in this area from compression to extension. The results enhance our understanding of the evolution of the Paleo-Asian Ocean.